2014
DOI: 10.2140/ant.2014.8.1201
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahedral elliptic curves and the local-global principle for isogenies

Abstract: We study the failure of a local-global principle for the existence of l-isogenies for elliptic curves over number fields K. Sutherland has shown that over ‫ޑ‬ there is just one failure, which occurs for l D 7 and a unique j -invariant, and has given a classification of such failures when K does not contain the quadratic subfield of the l-th cyclotomic field. In this paper we provide a classification of failures for number fields which do contain this quadratic field, and we find a new "exceptional" source of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 18 publications
1
51
0
Order By: Relevance
“…As far as we are aware, such methods have only been applied to curves of genus 2 and 3, and our computations for the three curves in (2) pushes these methods to their limit. In Sections 12, 13, 14 we determine the quadratic points on the three modular curves in (2), and deduce modularity of the non-cuspidal real quadratic points.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…As far as we are aware, such methods have only been applied to curves of genus 2 and 3, and our computations for the three curves in (2) pushes these methods to their limit. In Sections 12, 13, 14 we determine the quadratic points on the three modular curves in (2), and deduce modularity of the non-cuspidal real quadratic points.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…We would like to show that J(Q) = C, and for this it is enough to show that J(Q) [2] = C[2] = (Z 2Z) 3 . However for all primes p ∤ N we tried J(F p ) [2] = (Z 2Z) 6 or (Z 2Z) 4 , and so it does not seem to be possible to prove the desired conclusion using reduction modulo primes. Instead we will compute the entire mod 2 representation of J ρ J,2 ∶ Gal(Q Q) → Sp 6 (F 2 ) and use this to deduce that J(Q) [2] = (Z 2Z) 3 .…”
Section: 5mentioning
confidence: 99%
“…Banwait and Cremona [BC14] have shown that X G 7,13 (13) is isomorphic to the genus 3 curve C ′ defined in P 2 Q with equation 4x 3 y − 3x 2 y 2 + 3xy 3 − x 3 z + 16x 2 yz − 11xy 2 z + 5y 3 z + 3x 2 z 2 + 9xyz 2 + y 2 z 2 + xz 3 + 2yz 3 = 0.…”
Section: Analysis Of Rational Points -Higher Genusmentioning
confidence: 99%